Forest plantation mapping in the Southern Highlands, Tanzania 2016: reference point data set - Koskinen, Joni; Leinonen, Ulpu; Vollrath, Andreas; Ortmann, Antonia; Lindquist, Erik J; d'Annunzio, Remi; Pekkarinen, Anssi; Käyhkö, Niina (In supplement to: Koskinen, J et al. (2019): Participatory mapping of forest plantations with Open Foris and Google Earth Engine. ISPRS Journal of Photogrammetry and Remote Sensing, 148, 63-74, https://doi.org/10.1016/j.isprsjprs.2018.12.011, 2018)
Reference point data set of Southern Highlands land use / land cover, collected in a participatory mapping event, Mapathon, in Tanzania, October 2016, using Google Earth / Collect Earth software, later used in the final forest plantation classification